An Efficient Boron Source Activation Strategy for the Low-Temperature Synthesis of Boron Nitride Nanotubes - Ying Wang; Kai Zhang; Liping Ding; Liyun Wu; E Songfeng; Qian He; Nanyang Wang; Hui Zuo; Zhengyang Zhou; Feng Ding; Yue Hu; Jin Zhang; et al. (Nano-Micro Letters)
Highlights Developed more efficient boron activation strategies, while establishing various low-melting growth systems. The preparation temperature of boron nitride nanotubes has been reduced to 850 °C.